Cost-profit analysis of multilateral recycling system in Asia. (4th August 2009) - Kondoh, Shinsuke; Kuwatani, Masayuki; Fujimoto, Jun; Umeda, Yasushi
The objective of this study is to clarify quantitatively the driving force of multilateral recycling system in Asia, especially focusing on economic factors. To this end, we proposed a cost-profit analysis model for multilateral recycling system considering the differentials of economic factors between developed and developing countries at first. Based on this model, we conducted cost-profit analysis of multilateral recycling of four electronic products, namely, refrigerator, television, air conditioner and personal computer, to identify dominant economic drivers of multilateral recycling system in Asia. The result of analysis showed that high profitability and recycling ratio can be achieved by multilateral recycling system in spite of its extra transportation cost, mainly due to low labour cost in developing countries.